Makna Komunikasi Ritual dalam Praktik Kahik Malar pada Suku Tetun Belu - Donna Isra SIlaban; Mikhael Rajamuda Bataona; Marianus Diaz Yanto; Aprilia Kuth; Maria Lelugoa (WACANA: Jurnal Ilmiah Ilmu Komunikasi, 2026)
This study examines the meaning of ritual communication in the Kahik Malar practice of the Tetun tribe in Belu, East Nusa Tenggara. Kahik Malar is a healing tradition believed to recall the souls of accident victims. Using a qualitative descriptive method with an interpretive paradigm and James W. Carey's theory of ritual communication, this study aims to understand the meaning of messages within the context of the ritual. Data were collected through in-depth interviews, observations, and literature studies. The results show that ritual communication in Kahik Malar does not only focus on the transfer of information, but rather emphasizes sharing a common culture and strengthening collective identity. This is evident in the collective involvement of the community, the use of the symbolic Tetun language, and the utilization of various ritual media such as cotton, koba, white chicken, bamboo twigs, and thread, each of which has a special meaning. This ritual serves as a means to strengthen social solidarity, preserve cultural values, and strengthen the belief system of the Belu community. This study provides an in-depth understanding of the meaning of the spiritual ritual of Kahik Malar as an integral part of local culture that needs to be preserved.